Analisis Kualitas Software IRP (Integrated Resource Planning) Material Ticket Pengaruhnya Terhadap Kepuasan User Directorat Inventory Aerostructure DI PT. Dirgantara Indonesia (PERSERO) - R Fenny Syafariani; Khaerul Saputra (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2011)
Information System IRP (Integrated Resource Planning) is an application that aims to facilitate the process of activities at PT. DIRGANTARA INDONESIA (Persero), the system is implemented to improve the performance of the company. And in this case required IRP education to employees, so the employee knows that information systems running, to test the effects of software quality materials IRP Ticket to user satisfaction. The purpose of this research is to determine which information systems work, To know the employee response to the Integrated Information System for Resource Planning (IRP) Material Ticket, To know the effect of software quality materials Ticket IRP system to the level of user satisfaction in Directorat Inventory Aerostructure division, to find out how user satisfaction of information systems users IRP Material TicketThe method used in this study is qualitative and quantitative, to know that walking IRP Material Ticket using UML (Unified Modeling Language). Data collection techniques using literature study, observation, interviews, questionnaires, and, analyzing data using Analysis of Pearson Product Moment Correlation, Regression Testing, Determination coefficient, and z test, data processing using SPSS 14.0 for Windows.The results showed that the quality of materials Ticket IRP software has no effect on user satisfaction, it means showing that the higher the quality of the user software will not necessarily satisfied.